Respuesta :

the answer to your question is D) 3

Answer:

[tex] x_1 = \frac{-(-7) - \sqrt{(-7)^2 -4(1)(12)}}{2(1)}= \frac{7-1}{2}= 3[/tex]

[tex] x_2 = \frac{-(-7) + \sqrt{(-7)^2 -4(1)(12)}}{2(1)}= \frac{7+1}{2}= 4[/tex]

So then since we want the lesser root the correct answer on this case is:

D) 3

Step-by-step explanation:

For this case we have the followin expression:

[tex] x^2 -7x +12=0[/tex]

For this case we can use the quadratic formula in order to solve it, given by:

[tex] x = \frac{-b \pm \sqrt{b^2 -4ac}}{2a}[/tex]

And on this case a = 1, b = -7, c = 12. And if we replace we got:

[tex] x_1 = \frac{-(-7) - \sqrt{(-7)^2 -4(1)(12)}}{2(1)}= \frac{7-1}{2}= 3[/tex]

[tex] x_2 = \frac{-(-7) + \sqrt{(-7)^2 -4(1)(12)}}{2(1)}= \frac{7+1}{2}= 4[/tex]

So then since we want the lesser root the correct answer on this case is:

D) 3